The Utilization of the Camtasia Application in Making the Human Respiratory System Science Learning Media - Mohd Noor, Ahmad Firdaus; Adhe Octaviandra; Azza Hassan Mohamed Hussein (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Camtasia is a software used to record screens and record voices to create interactive menus and create media presentations produced by Techsmith. This application can be used to create online-based learning media, namely making video tutorials or training to be presented. This article contains procedures for using the Camtasia application which aims to create learning media and aims to produce learning media that will be useful for achieving learning goals. The use of the Camtasia application is also very suitable to be applied at this time because the Indonesian education system already has to use a distance learning system. It is hoped that the making of this learning media video will later get a good response from students. The stages of using Camtasia application in this article are 1) Camtasia application, 2) Camtasia application features, 3) How to use Camtasia application, 4) Camtasia application use in making learning media, 5) Camtasia advantages and disadvantages.